Combining transcriptomics with network pharmacology to explore the mechanism of Yiqi Huoxue decoction against liver fibrosis - Yao-Yao Mao; Ke Zhang; Dan-Dan Zhao; Jia-Wei Cui; Zhan-Dong Lin; Cong-Yue Zhang; Yue-Min Nan (PLoS ONE, 2025)
Background Clinical practice commonly uses the Yi-qi Huo-xue formula (YQHX), a traditional Chinese herbal medicine comprising eight herbal components, to treat liver fibrosis resulting from various etiologies. Nevertheless, this formula’s specific active constituents and underlying mechanisms of action remain to be fully elucidated. Methods The drug components of YQHX and potential targets for liver fibrosis were identified via the screening of the various databases. Qualitative and quantitative identification of chemical components of drug-containing serum by Ultra Performance Liquid Chromatography (UPLC).Liver fibrosis was induced in mice through the intraperitoneal injection of carbon tetrachloride, followed by oral administration of YQHX. RNA-Seq quantified transcriptomic profiles in liver tissue.The degree of liver fibrosis was assessed via histopathology staining, the transcription and expression of relevant proteins were analyzed. Primary cells were isolated for in vitro experiments to validate the influence of YQHX on the associated signaling pathways. Results Network pharmacology identified IL-1β, IL-6, and TNF-α as potential targets for YQHX in treating liver fibrosis.The UPLC detected multiple potential active components. In vivo experiments showed that YQHX reduced serum AST and ALT levels in liver fibrosis-induced mice, decreased liverIL-1β, IL-6, and TNF-α levels, and improved liver fibrosis.The results of transcriptomics suggest that YQHX can reduce the expression of “collagen-activated signaling pathway,” “MyD88-dependent toll-like receptor signaling pathway,” “fibrinolysis” and “toll-like receptor 4 signaling pathway”. Furthermore, YQHX reduced the aggregation of M1 macrophages in the portal area and the deposition of α-SMA. Primary bone marrow-derived cells successfully transformed into M1 macrophages after induction, and YQHX reduced the levels of IL-1β, IL-6, and TNF-α in the supernatant of M1 macrophage culture and decreased the activation of primary hepatic stellate cells indirectly co-cultured with the supernatant. Interestingly, TLR4 agonists weakened this inhibitory effect. Both in vitro and in vivo experiments demonstrated that YQHX could inhibit the expression of the TLR4/TRAF6/MyD88 pathway in M1 macrophages. Conclusion We reveal here the molecular mechanism and signaling pathway of YQHX in treating liver fibrosis by utilizing network pharmacology in conjunction with in vivo and in vitro experiments. The findings offer insights that may advance the clinical application of YQHX.